2019
DOI: 10.15405/epsbs.2019.02.02.14
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing In Climbing And Psychological Effects Of Sport Climbing

Abstract: A contemporary demands in adrenaline sport activities emphasize risk, danger and adrenaline on one hand, and desire for individual feelings of happiness on the other hand. The study analysed if sport climbing can influence common feelings and psychological states, in terms of proportional representation of the selected positive and negative indicators. The purpose of the study was to characterize experiencing in climbing and to find out psychological effects of a 3-month sport climbing course on individualized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a large (but representativeness unknown) sample of Chinese climbers, Ding and Schuett's (2013) medium quality study reported that their main motivations for climbing included 'resting the mind', 'tranquillity' and 'releasing tension', whereas the social aspect of the sport was less important in this population. In two low quality surveys of non-climbers who participated in climbing courses, some improvements were reported on participants' psychological wellbeing, including improvements in feelings of discomfort and self-esteem (Hrušová & Chaloupská, 2019;Kessell, 1994). Four medium to high quality studies assessed associations between anxiety and climbing performance, with mixed findings (Bailey et al, 2019;Bazancir et al, 2018;Feher et al, 1998;Sanchez et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large (but representativeness unknown) sample of Chinese climbers, Ding and Schuett's (2013) medium quality study reported that their main motivations for climbing included 'resting the mind', 'tranquillity' and 'releasing tension', whereas the social aspect of the sport was less important in this population. In two low quality surveys of non-climbers who participated in climbing courses, some improvements were reported on participants' psychological wellbeing, including improvements in feelings of discomfort and self-esteem (Hrušová & Chaloupská, 2019;Kessell, 1994). Four medium to high quality studies assessed associations between anxiety and climbing performance, with mixed findings (Bailey et al, 2019;Bazancir et al, 2018;Feher et al, 1998;Sanchez et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Two additional studies compared climbers to nonclimbers to investigate differences in life satisfaction and stress resistance (Ardahan & Mert, 2013;Tukaiev et al, 2020, respectively). One study surveyed university students who had attended a 3-month indoor climbing course for beginners, to assess impact of climbing on psychological wellbeing (Hrušová & Chaloupská, 2019). One study surveyed gynaecological cancer survivors to assess participation and interest in rock-climbing and possible associations with posttraumatic growth (Crawford et al, 2015).…”
Section: Samplesmentioning
confidence: 99%
“…According to some authors [18,19], outdoor activities, being very involving, may have a high geoeducation potential for communicating and explaining geodiversity and Earth's history [16,19] and to induce forms of place-based learning, as suggested for young generations by Gordon et al [6]. Moreover, they could be a potential tool to achieve social and health goals (i.e., SDGs n. 3) (e.g., [21][22][23]). All outdoor activities, despite providing all these benefits, may be affected by different types of natural hazards (e.g., rock falls; [24]).…”
Section: Introductionmentioning
confidence: 99%
“…Since the antidepressant effect of physical exercise has been shown to be comparable to psychotherapy and antidepressant psychotropic drugs [ 9 11 ], current guidelines additionally recommend physical activity [ 2 , 8 ]. As bouldering/climbing has proven its positive impact on psychological wellbeing [ 12 , 13 ], concepts of “therapeutic climbing” are gaining interest in depression treatment. Recent systematic reviews suggest that it might be the most important step to get patients involved into a therapeutic program as differences between the different approaches are small [ 14 ].…”
Section: Introductionmentioning
confidence: 99%